MacIntyre's After Virtue at 40 - Angier, Tom 1970- (Cambridge University Press, 2023)
Since its publication in 1981, Alasdair MacIntyre's After Virtue has been recognised as a classic. Primarily a work of moral philosophy, it also draws on sociology, classics, political science and theology to effect a unique intellectual synthesis, and its combination of erudition and challenging, even provocative argument has made a significant impact throughout the humanities disciplines. This volume of new essays unpacks the influence of After Virtue on ethical and political theory, sociology and theology, and offers a multi-faceted exploration of its significance. The essays offer a way into MacIntyre's philosophy, and demonstrate how, rather than waning in influence over the past forty years, his most seminal text has found an ever-wider audience and continues to inspire controversy and debate in the humanities
Title from publisher's bibliographic system (viewed on 13 Oct 2023)
Aftervirtue and virtue ethics / Tom Angier -- After virtue and happiness / Jennifer Herdt -- After virtue : Nietzsche or Aristotle, institutions and practices / Kelvin Knight -- After virtue's critique of liberalism / David Rondel -- After virtue and the rise of postliberalism / Nathan Pinkoski -- After virtue and conservativism / David McPherson -- After virtue as a real utopia / Jason Blakely -- Form, style, and voice in After virtue / Stephen Mulhall -- After virtue, narrative, and the human good / Micah Lott -- After virtue as a narrative of revolutionary practical reason / Christopher Lutz -- Theological overtones in After virtue / Charles Pinches -- Law as social practice : After virtue and legal theory / Mark Retter -- After virtue, managers and business ethics / Paul Blackledge
Keywords: MacIntyre, Alasdair C. / After virtue; MacIntyre, Alasdair C. / Criticism and interpretation; MacIntyre, Alasdair C. -- 1929- -- After virtue; Virtue; Ethics; Aufsatzsammlung